2018
DOI: 10.1007/s12070-018-1386-4
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Screening for Prevalence of Hearing Impairment in Rural Areas

Abstract: Hearing is one of the most important sense organs for man. Hearing loss is often associated with delayed speech and language development in young children. Early identification and intervention improves the chance a child gets to lesser delays in development and improving the overall quality of life. To find out the prevalence of hearing loss in neonates in the rural taluka of Maval, Pune, Maharashtra, India. Prospective Non Randomized Clinical Study. The study was carried out between April 2012 and April 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
11
2
Order By: Relevance
“…We found that the prevalence of HL for babies admitted to the NICU was 1.5% which is comparable with the results of the study done by Khairi et al 4 . However, our prevalence was lower compared to other studies 3,9 . The low prevalence may be explained by the low number of babies (49%) who had completed the diagnostic test.…”
Section: Hearing Losscontrasting
confidence: 91%
See 1 more Smart Citation
“…We found that the prevalence of HL for babies admitted to the NICU was 1.5% which is comparable with the results of the study done by Khairi et al 4 . However, our prevalence was lower compared to other studies 3,9 . The low prevalence may be explained by the low number of babies (49%) who had completed the diagnostic test.…”
Section: Hearing Losscontrasting
confidence: 91%
“…Babies requiring intensive care in the Neonatal Intensive Care Unit (NICU) were reported to have a higher prevalence of HL, involving up to 46% of newborns admitted to the NICU 2 . In 2018, Parab et al 3 reported a higher prevalence of HL amongst high risk babies, as 10.6 per 1000 high risk births compared to healthy neonates. A study in Malaysia in 2005 reported that 1% of high risk neonates in the NICU had HL 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Stay at NICU, mechanical ventilation, ototoxic drug (aminoglycoside exposure), oxygen need and history of deafness in the family positively correlated with the hearing loss. No significant association between hearing loss and congenital disease (cytomegalovirus), bacterial meningitis, streptococcus positivity, loop diuretic exposure and ECMO [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hearing impairment in neonates ranged from 1.59 to 8.8 per 1000 screened in studies where auditory brainstem response audiometry (ABR) was done after failing otoacoustic emission (OAE) twice. [13][14][15][19][20][21][22] ABR (AABR) double screening, followed by a conventional ABR or auditory steady state response (ASSR) audiometry showed a similar frequency of 2.2-4.1 per 1000. 16,18 A single OAE followed by ABR showed a much higher failure rate of 22.1/ 1000, falling to 1.42/1000 bilateral HL after a complete audiological assessment.…”
Section: Neonatal Screeningmentioning
confidence: 99%
“…Hearing impairment in neonates with risk factors ranged from 7 to 49.18 per 1000. [13][14][15]19,22 Neonatal intensive care unit admissions, mechanical ventilation, low birth weight, prematurity, hyperbilirubinaemia, congenital anomalies or syndromes and family history of HL were the most common factors used to identify at-risk infants. Dar et al 21 noted that cytomegalovirus causes a 20-fold increase in early onset or congenital HL.…”
Section: Neonatal Screeningmentioning
confidence: 99%